Determinants of Service Quality in High-end IT Enabled Services: An Indian Perspective - Srivastava, Vandana; ., A.Sharfuddin; ., Sanjeev Kishore (Information Management and Business Review, 2012)
IT enabled Services (ITeS) have charted tremendous growth in India over the last two decades. Over the years, the service domain has evolved to include high-end services as well as traditional services. Along with fresh opportunities, the evolving service landscape brings new challenges for the service providers, with quality being the prime challenge. As the nature of services change, new determinants of service quality emerge. Towards this aim, this research paper presents a fresh perspective of determinants of service quality in high-end ITeS by integrating elements from traditional service quality models and frameworks with issues related to technology and organizational relationship management. The research involves a two-phase study. Findings from the literature survey and a qualitative study are used to identify the determinants of service quality and to create a hypothetical model. Based on data collected from senior executives of Indian service providers, the second phase of the study presents a regression model of the determinants. The combined linear effects of the determinants were found to account for 76.8% of the variation in success of high-end ITeS projects. The regression model highlights the critical and significant role played by Knowledge Management, Technology Management and Service Design and Delivery in service quality. The findings further highlight the potential of mechanisms for capturing and re-using organizational learning in reducing service quality gaps. The strategic implications presented in the paper will provide a starting point for service providers aiming to engage in providing high-end IT-enabled Services.